Importance of preclinical evaluation of wear in hip implant designs using simulator machines - Rafael Mello Trommer; Márcia Marie Maru (Revista Brasileira de Ortopedia)
ABSTRACT Total hip arthroplasty (THA) is a surgical procedure that involves the replacement of the damaged joint of the hip by an artificial device. Despite the recognized clinical success of hip implants, wear of the articulating surfaces remains as one of the critical issues influencing performance. Common material combinations used in hip designs comprise metal-on-polymer (MoP), ceramic-on-polymer (CoP), metal-on-metal (MoM), and ceramic-on-ceramic (CoC). However, when the design of the hip implant is concerned besides the materials used, several parameters can influence its wear performance. In this scenario, where the safety and efficacy for the patient are the main issues, it is fundamental to evaluate and predict the wear rate of the hip implant design before its use in THA. This is one of the issues that should be taken into account in the preclinical evaluation step of the product, in which simulated laboratory tests are necessary. However, it is fundamental that the applied motions and loads can reproduce the wear mechanisms physiologically observed in the patient. To replicate the in vivo angular displacements and loadings, special machines known as joint simulators are employed. This article focuses on the main characteristics related to the wear simulation of hip implants using mechanical simulators, giving information to surgeons, researchers, regulatory bodies, etc., about the importance of preclinical wear evaluation. A critical analysis is performed on the differences in the principles of operation of simulators and their effects on the final results, and about future trends in wear simulation.